Factors associated with adolescent pregnancy in the Sunyani Municipality of Ghana - Bernard Yeboah-Asiamah Asare; Diana Baafi; Bismark Dwumfour-Asare; Abdul-Razak Adam (Elsevier, 2019)
Adolescent pregnancy is an important social and public health issue worldwide, and it is linked to several social and economic consequences. This study sought to investigate the factors associated with adolescent pregnancy in the Sunyani municipality of Ghana. This study was an unmatched case-control among adolescents aged 15-19 years. The cases were pregnant and parenting adolescents, and controls were non-pregnant adolescents with no birth experience. Data were collected from 245 participants (120 cases and 125 controls) through a structured questionnaire survey and analysed with STATA version 12 for risk factors of adolescent pregnancy using Pearson's chi-square test and logistic regression.The average age of study participants was 16.9 ± 1.15 years. Place of residence, occupation and economic status were found to be associated with adolescent pregnancy. Multiple logistic regression revealed that adolescents from urban settings, Abesim zone (OR = 0.07, 95% CI 0.01-0.35), and New Dormaa zone (OR = 0.19, 95% CI 0.05-0.77) had decreased odds of adolescent pregnancy compared to their rural counterpart-Antwikrom zone. Adolescents were also at increased odds of becoming pregnant when they were into apprenticeships (OR = 9.77, 95% CI 2.00-47.75) or unemployed (OR = 11.69, 95% CI 4.47-30.58) than being in school. Adolescents with low economic background (OR = 4.05, 95% CI 1.43-11.52) were 4.1 times more likely to get pregnant compared to those with high economic status.Key factors associated with adolescent pregnancy have been established and these need attention from all stakeholders to forestall public and social health safety among adolescents. Keywords: Adolescent pregnancy, Case control, Sunyani, Ghana